Socialization of Empowerment Strategies and Optimization of Employee Engagement in Azizah Crackers MSME - Alfian; Henryanto Abaharis; Jhon Fernos; Romi Susanto; Juarsa Badri; Zusmawati (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to increase the understanding of business owners and employees regarding employee empowerment and employee engagement, as well as to strengthen employee participation in supporting business development. The activity was conducted at Azizah Crackers MSME in Indarung, Lubuk Kilangan District, Padang City. The main issues identified were the limited involvement of employees in business development activities and their lack of understanding of the strategic role of human resources in organizational sustainability. The program was implemented through preparation, lectures, discussions, question-and-answer sessions, and mentoring activities. The outcomes of the activity were evaluated through direct observation and participant responses during the implementation process. The findings showed that participants actively engaged in discussions, shared experiences related to workplace challenges, and demonstrated a better understanding of employee empowerment and employee engagement concepts. The activity also facilitated more open communication between the business owner and employees regarding their roles and contributions to business development. These findings suggest that empowerment-based socialization activities can serve as an initial step in fostering employee participation, collaboration, and awareness of the importance of human resources in supporting MSME sustainability and competitiveness.